2014
DOI: 10.1371/journal.ppat.1004389
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Secretion and Metabotropic Glutamate Receptor 1 Expression during Kaposi's Sarcoma-Associated Herpesvirus Infection Promotes Cell Proliferation

Abstract: Kaposi's sarcoma associated herpesvirus (KSHV) is etiologically associated with endothelial Kaposi's sarcoma (KS) and B-cell proliferative primary effusion lymphoma (PEL), common malignancies seen in immunocompromised HIV-1 infected patients. The progression of these cancers occurs by the proliferation of cells latently infected with KSHV, which is highly dependent on autocrine and paracrine factors secreted from the infected cells. Glutamate and glutamate receptors have emerged as key regulators of intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…Earlier studies have shown the crucial roles of several KSHV latent proteins in regulating cellular processes to make the environment conducive to viral infection (26,41,44). We have previously shown that kaposin A, which is one of the proteins expressed during KSHV latency, played crucial roles in KSHV-induced cell proliferation by activating metabotropic glutamate receptor 1 (mGluR1) during KSHV infection (41). Kaposin A has also been shown to mediate oncogenesis in vitro in Rat3 fibroblasts and in nude mice (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies have shown the crucial roles of several KSHV latent proteins in regulating cellular processes to make the environment conducive to viral infection (26,41,44). We have previously shown that kaposin A, which is one of the proteins expressed during KSHV latency, played crucial roles in KSHV-induced cell proliferation by activating metabotropic glutamate receptor 1 (mGluR1) during KSHV infection (41). Kaposin A has also been shown to mediate oncogenesis in vitro in Rat3 fibroblasts and in nude mice (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of HACE1 during de novo infection of endothelial cells, in KSHV latently infected TIVE-LTC and BCBL-1 cells as well as in the KS tissues, suggests that HACE1 is important for the biology of KSHV. Earlier studies have shown the crucial roles of several KSHV latent proteins in regulating cellular processes to make the environment conducive to viral infection (26,41,44). We have previously shown that kaposin A, which is one of the proteins expressed during KSHV latency, played crucial roles in KSHV-induced cell proliferation by activating metabotropic glutamate receptor 1 (mGluR1) during KSHV infection (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subcellular fractionation and cell membrane preparation were performed as described previously (18,35). Briefly, cells were homogenized with a Dounce homogenizer in homogenization buffer (250 mM sucrose, 20 mM HEPES, 10 mM KCl, 1 mM EDTA, 1 mM EGTA, and protease inhibitors).…”
Section: Cells and Virusmentioning
confidence: 99%